UPAYA MENINGKATKAN JUMLAH WAKTU AKTIF BELAJAR SISWA MELALUI PERMAINAN SOCCER LIKE GAMES DALAM PEMBELAJARAN SEPAKBOLA - Yanto Gunawan, - (2020)
ABSTRACK Yanto Gunawan (1606050). Efforts to Increase the Amount of Active Learning Time of Students Through Soccer Like Games in Soccer Learning. Under the guidance of Carsiwan, M.Pd and Dr. Nuryadi, M.Pd. The study is based on the insufficient amount of student's active learning time in the physical education program of SMK Negeri 8 Bandung primarily in soccer learning. The purpose of the study is to increase student's active learning time (ALT) by implementing soccer like games strategy. The method used in the study is Classroom Action Research (CAR) with the research design of Kurt Lewin's Model which consists of two cycles where each cycle includes planning, action, observing, reflecting and duration recording in order to find out the amount of active learning time done by the students. The subjects of the study are 31 tenth-grader students from X TEI 2 class. The results of preliminary observations show that the level of students' active learning is exceptionally low on (44,4%). On the first cycle I action I observation, the amount of students' active learning time showed an increase to (48.8%). Then, cycle I action II revealed a decrease in students' active learning time to (42.2%). Cycle II action I showed that students' active learning time amount increased to (56.6%). On cycle II action II, the amount of active learning time reached (72.2%). Based on the research data of the study, it can be concluded that there is a significant percentage increase in each cycle and action which indicates that soccer like games in soccer learning can increase students' active learning time. Keywords: soccer like games, football, active learning time.